EVOLUTIVE ASPECTS OF FLEXIBLE ACRYLATES SUPERPOSABLE ON GENERAL STATUS OF THE PATIENTS - Irina Gradinaru; Loredana Hurjui; Andreea Clim; Costin Chirica; Magda-Ecaterina Antohe (Romanian Dental Association for Education, 2019)
The purpose of this study is to restore to the foreground an essential issue of the dental medical practice, namely the therapy by means of mobilizable prostheses in allergic patients or with rheumatic degenerative diseases, which affect the manual mobility. The functional advantages of flexible materials are somewhat less obvious. Thermoplastic resins are stable, resistant to polymerization and contain very small amounts of free monomer, which in some products may be missing. A significant percentage of the population is allergic to the free monomer and these materials offer a new treatment alternative for these people. In addition, thermoplastic resins have a reduced porosity, resulting in reduced bacterial adhesion and improved color stability.The key to the functional benefits is the flexibility of the material that helps in the dispersion of the force of weight through the adapted characteristics of the design of the basic material.